Identitas nasional di era digital: Tantangan dan peluang bagi gen Z - khumaeroh, siti (Maliki Interdisciplinary Journal, 2026)
The rapid advancement of digital technology has posed serious challenges to the sustainability of national identity, particularly among Generation Z, who have grown up entirely within a digital ecosystem. This study aims to analyze the dynamics of national identity among Generation Z in the digital era, identify the factors contributing to the weakening of national consciousness, and map the strategic challenges and opportunities for its strengthening. The research employs a library research approach through the review of relevant academic journals, reference books, and policy documents. The findings reveal that Generation Z possesses an open, creative, and critical character, yet faces an identity crisis triggered by the dominance of foreign cultures through social media, insufficient internalization of national values in civic education, and rising individualism and consumerism. Conversely, the digital era also presents significant opportunities through the use of social media as a platform for promoting local wisdom and disseminating contextual national narratives. This study concludes that strengthening Generation Z's national identity requires an adaptive, technology-based approach that positions Pancasila as a dynamic cultural filter, supported by synergy among the government, educational institutions, and local content creators..